Women’s empowering through sharia crowdfunding - Bayu Wardhana; Muhammad Amirul Mukminin; Izza Syafira; Retty Isnawati; Fitri Nur Latifah (Jurnal Inovasi Ekonomi, 2020)
The contribution of women entrepreneurship in the economy cannot be underestimated, but the bias in funding approvals is still an issue. In addition, Indonesia, with its majority Muslim population, also faces challenges to make a financial platform that does not conflict with Islamic law. Based on these problems, this paper offers a solution for developing a sharia-based financing model that focuses on women empowerment through crowdfunding.